Diseño de un sistema de control de flujo de aire en un colector solar. - Tigse Tigse, Alex Leonardo (2021)
The development of this research contributes to the study of cocoa drying through solar collectors, being the flow control necessary to push the concentrated heat inside the collector, due to this the importance of maintaining a constant flow inside the collector is born, To do so, perform an analysis using characteristic curves where the behavior of temperature and flow at the outlet of the collector is evidenced. In the project, several factors were planned, such as the fact of not having a Programmable Logic Controller (PLC) due to its high cost, that is why a more accessible microcontroller was implemented such as the Arduino Nano board, which complies with the same conditions as any other controller, for this the microcontroller receives the main signals such as temperature and airflow, to carry out a PID control with the airflow variable, in the same way with the help of the MAF sensor, which It is a type of sensor used in the automotive part, specifically in the intake system, it performs the airflow and temperature readings which provide electrical signals from 0 to 5 Volts allowing data to be entered to the microcontroller as an analog input that to Through proper programming, the flow data can be displayed on an LCD. In the present investigation, serial communication between microcontrollers is implemented, which performs power control through a keyboard and PID control to determine the behavior of the temperature at the collector outlet. The method of tuning the PID behavior is empirically conditioned resulting in a stabilization automatically at a different set point. Using the statistical calculation of the Chi-square, the relationship between the two variables is analyzed so that it is verified that if the mass flow of air at the outlet temperature of the solar collector influences considerably.